The macroanatomical investigations on the aortic arch in porcupines (Hystrix cristata) - Atalar, Ö; Yilmaz, S; Burma, O; Ilkay, E (Blackwell Verlag Gmbh, 2003)
The anatomy of aortic arch in porcupine was studied. Angiography was applied to each of the three adult porcupines (two males, one female) following the injection of latex from the abdominal aorta for the examination of aortic arch. The results indicated that three arteries arose from aortic arch in porcupine. These were truncus brachiocephalicus, arteria carotis communis sinistra and arteria subclavia sinistra. The truncus brachiocephalicus in porcupine yielded arteria subclavia dextra and arteria carotis communis dextra. Truncus bicaroticus was absent. The origin of truncus costocervicalis (right) and arteria vertebralis (right) arose from a common root. Left or right axillary arteries seemed to be a continuation of subclavian arteries. The results of this study may contribute to the data in this area of science.